Pemurnian dan Karakterisasi Enzim Lipase dari Aspergillus oryzae pada Kopra Berjamur - Dali, Seniwati Dali; Patong, Abdul Rauf; Jalaluddin, Muhammad Noor; Parenrengi, Pirman Andi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2011)
An investigation on purification and characterization of lipase enzyme production Aspergillus oryzae from copra by fermentation of oliveoil has been carried out. This enzyme can be produced by fermenting olive oil in a medium containing Aspergillus oryzae. Crude enzyme isobtained by centrifuging the medium cultures containing Aspergillus oryzae at 3500 rpm for 30 minutes and than adding 0.2 M borat buffer(pH 8.2). Enzyme activity was determined from paranitrophenol as product of lipase catalysis of paranitrophenylbutirat (0.2 M) assubstrate measured by the Vorderwulbecke method. Prepurification process was by ammonium sulphate fractionation. Precipitation60-80% ammonium sulphate produced maximum activity of enzyme. Purification by Q sepharosa FF and sephadex G-75 collumchromatography produced four and three fractions with purifity of 12.85 and 20.25 times than crude enzyme respectively. Characterizationof this enzyme showed optimum condition at pH 8.2, temperature at 350C, the Km value at 0.046 M, and Vmaks is 1.926 μmol/menit and themolecular weight at 40.7 kDa.